2D Electronics: Electronic Devices and Circuits Based on Wafer‐Scale Polycrystalline Monolayer MoS2 by Chemical Vapor Deposition (Adv. Electron. Mater. 8/2019). (8th August 2019) - Wang, Lin; Chen, Li; Wong, Swee Liang; Huang, Xin; Liao, Wugang; Zhu, Chunxiang; Lim, Yee‐Fun; Li, Dabing; Liu, Xinke; Chi, Dongzhi; Ang, Kah‐Wee
Abstract : In article number1900393, Xinke Liu, Dongzhi Chi, Kah‐Wee Ang, and co‐workers report the demonstration of diverse electronic building blocks including field‐effect transistors, logic gates, and memristors. These building blocks are based upon wafer‐scale monolayer MoS2 synthesized via a scalable chemical vapor deposition technique. By virtue of a fully complementary metal‐oxide‐semiconductor‐compatible fabrication process, this work paves the way toward unleashing the potential of atomically thin MoS2 for practical next‐generation ultrathin electronics.